AVALIAÇÃO DE CARACTERÍSTICAS BIOLÓGICAS DE TRICHOGRAMMA PRETIOSUM RILEY (HYMENOPTERA: TRICHOGRAMMATIDAE) CRIADO EM TRÊS HOSPEDEIROS - Volpe, H.x.l. [UNESP]; Bortoli, S.a. De [UNESP]; Thuler, R.t. [UNESP]; Viana, C.l.t.p. [UNESP]; Goulart, R.m. [UNESP] (Instituto Biológico, 2022)
Trichogramma genus are very important on biological control, since that its potential was discovered, its very useful worldwide as a option for pest control in different agroecosystems, making indispensable the knowledge of different hosts for these parasitoids. The aim of this work was to evaluate T. pretiosum specificity in relation to three host species. The research was conducted at Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal (FCAV-UNESP), in the Laboratório de Biologia e Criação de Insetos. It was realized test of choice (no choice) in relation to Anagasta kuehniella, Spodoptera frugiperda and Plutella xylostella eggs handled under laboratory conditions. By the tests it was possible to verify differences for the number of parasitized eggs, being A. kuehniella preferred in the first and second generation, but no differences were founded for adults emergence. In the second generation, the higher number of parasitized eggs was observed for Anagasta kuehniella and Spodoptera frugiperda, differing of Plutella xylostella. By the results its possible to conclude that T. pretiosum Tp – 8 strain had better adaptation to the host A. kuehniella and the strain of Trichogramma pretiosum was viable to be used in Biological Control programs, to control Spodoptera frugiperda and Plutella xylostella.

A importância do gênero Trichogramma no controle biológico tem intensificado sua utilização em muitos países, tornando cada vez mais relevante o conhecimento de seus hospedeiros. Dessa maneira, objetivou-se com este trabalho avaliar a especificidade de Trichogramma pretiosum em relação a três espécies hospedeiras habitualmente parasitadas, Anagasta kuehniella, Spodoptera frugiperda e Plutella xylostella. O ensaio foi realizado no Laboratório de Biologia e Criação de Insetos da Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal – UNESP. Foi realizado teste sem chance de escolha para o parasitóide em relação aos ovos daqueles hospedeiros. Verificou-se que para a primeira geração houve diferença significativa para o parâmetro biológico número de ovos parasitados, onde ovos de A. kuehniella foram os mais parasitados. Para a segunda geração, a porcentagem de emergência e o período de desenvolvimento ocorreu de forma análoga à da 1ª geração nos 3 hospedeiros, não havendo diferenças estatísticas entre os eles. O maior número de ovos parasitados foi observado para os hospedeiros A. kuehniella e S. frugiperda, diferindo estatisticamente de P. xylostella. Pelos resultados conclui-se que a linhagem Tp-8 de T. pretiosumtem melhor adaptação ao hospedeiro A. kuehniella apresentando condições para utilização em programas de controle biológico, tanto de S. frugiperda como de P. xylostella.
EVALUATION OF BIOLOGICAL CHARACTERISTIC OF TRICHOGRAMMA PRETIOSUM RILEY (HYMENOPTERA: TRICHOGRAMMATIDAE) CREATE IN THREE HOST
Keywords: Eggs parasitoid; biological control; Trichogrammatidae; Plutella xylostella; Spodoptera frugiperda; Anagasta kuehniella; Parasitóide de ovos; controle biológico; Trichogrammatidae; Plutella xylostella; Spodoptera frugiperda; Anagasta kuehniella